2022
DOI: 10.1017/cts.2022.424
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement education in academic health centers, colleges, and universities

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Our course was unique in being offered as a micro-course at a major public university's School of Public Health, focused on the rationale, principles, methods and challenges involved in community engagement practice more broadly but, as noted, doing so through an anti-racism lens. The course's pedagogical framework thus included classic CE principles, for example, starting with the community's issues and concerns and maintaining community ownership and control (Doubeni et al, 2022). Additionally, however, while many CE courses now also emphasize the importance of teaching about the Social Determinants of Health (SDoH), we believe that the particularly strong focus of our course on structural racism and viewing health and social issues through a prism that privileges the key role of racial discrimination and inequities, added important depth to such analysis.…”
Section: What This Course Addsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our course was unique in being offered as a micro-course at a major public university's School of Public Health, focused on the rationale, principles, methods and challenges involved in community engagement practice more broadly but, as noted, doing so through an anti-racism lens. The course's pedagogical framework thus included classic CE principles, for example, starting with the community's issues and concerns and maintaining community ownership and control (Doubeni et al, 2022). Additionally, however, while many CE courses now also emphasize the importance of teaching about the Social Determinants of Health (SDoH), we believe that the particularly strong focus of our course on structural racism and viewing health and social issues through a prism that privileges the key role of racial discrimination and inequities, added important depth to such analysis.…”
Section: What This Course Addsmentioning
confidence: 99%
“…With the exception of the substantial literature on academic-service learning (Brooks et al, 2019), however, we found relatively sparse attention specifically to the pedagogy of community engagement. Important exceptions include Doubeni et al (2022) article offering a useful pedagogical framework to support curriculum development for CE in research, education, and clinical care in academic health centers and universities and Levin et al's (2021) review of best practices in CE by schools and programs in public health. Levin and co-authors describe facilitators of successful academic efforts, including leadership, infrastructure, and culture, as well as challenges, including mistrust by community members, power dynamics, and unequal sharing of credit.…”
Section: Community Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…Best practices for pedagogy around community engagement includes four phases: preparation, action, reflection, and evaluation. These experiences require strong community partners as co-facilitators, a longitudinal trusting relationship between community and academic partners, and careful moderation of reflection/evaluation that centers community context ( 20 ). These on-the-ground experiences can be informed or supplemented by existing CBPR curricula ( 21 ).…”
Section: Introductionmentioning
confidence: 99%